Evaluating the Urban Landscape Regeneration Process: Aligning Policies and Realities - Menezes, Mariane; Rodrigues, Frederico Meireles (URBE. Arquitectura, Ciudad y Territorio, 2024)
This paper explores the synergy between European urban development programmes, specifically focusing on the Urban Development Strategic Plan (PEDU) within the context of the city of Vila Real, Portugal, with a spotlight on the Avenida Carvalho Araújo (ACA) Project. European policies, exemplified by initiatives like Europe 2020 and the European Structural and Investment Funds, underscore a commitment to sustainable, inclusive urban growth. The ACA Project, as a case study for urban regeneration, underwent an ex-post evaluation, considering aesthetic, social, and ecological values through a trivalent approach. Methodologically, the research incorporates case study analysis, interviews with stakeholders, and overall programme evaluation. Results showcase the alignment of PEDU objectives across various levels demonstrating the project's level of implementation. This paper contributes to understanding the efficacy of urban development programmes emphasizing the need for coherence between overarching policies and local needs. The ACA Project illustrates the potential of strategic urban interventions to elevate the quality of urban spaces and contribute to broader sustainability goals.